Pattern of infertility at LAUTECH teaching hospital, Ogbomoso, Nigeria. (2019)
Background and Objectiver Infertility is a socially destabilising health problem, which remains a cause of stigma and threat to couples desirous of conception in Nigeria. This sludy aimed to ecxamine the pattern of presentation and management outcome of infertility at LAUTECH Teaching Hospital (LTH), Ogbomoso. Methods A descriptive retrospective study of infertile couples attending the gynaecological clinicovera 3-yearpe-riod was conducted. Intonation on sociodemographic and gynaccological characteristics, medical history and management outcome was obtained from the medical reconls of the patients using a stctured proforma Data was analysed using SPSS version 20.0. Results The incidence of infertility was 34.30ol The mean age of the infertile women was 6.44 4.7 ycars. Secondary infertility/ accounted for the majority of the cases (73.0") with the_ mean duration of infertility being3,92 1 years. Male factor was identified in 10.4 of cases while female factor wasscen in 4L6"ot cases Both partners contributed to infertility in 34% while there was no identifiable cause in 14%. The commonest causes of infertility in the women were inadequate coital exposure, previous abnormal vaginal discharge and previous induced abortion representing 39.5%, 37.1%, and 33.7% respectively. Pregnancy was achieved in 3.0% of the women following treatment Conclusion The institutional incidence of infertility was high with a preponderance of secondary infertility. Pregnancy rate following conventional treatment was poor